Pengaruh Total Asset Turnover, Debt To Equity Ratio, Current Ratio, dan Firm Size Terhadap Return On Asset pada Perusahaan Manufaktur Subsektor Makanan dan Minuman yang Terdaftar di BEI Tahun 2016-2023 - Kurniasih, Reni; Merliana, Vina (Masyarakat Ekonomi Syariah Bogor, 2024)
For the period of 2016–2023, this study is to ascertain the impact of the following factors on return on assets: firm size, debt to equity ratio, total asset turnover, and current ratio in manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange. An approach to verification and description is combined with a quantitative methodology in this study. Numerous tests are used in statistical testing, including the traditional assumption test, multiple linear regression test, Pearson correlation coefficient test, determination coefficient test, and hypothesis test with partial and simultaneous tests (t and f tests). The Food and Beverage Sub-Sector Manufacturing enterprises employs 64 enterprises, whose financial records provide the sample data. In nonprobability sampling, purposeful sampling is used. Version 26.0 of IBM SPSS was the analysis tool used in this investigation . According to study results, return on assets is significantly impacted by the debt to equity ratio, but it is not affected at all by the current ratio, total asset turnover, or business size. Return on assets is significantly impacted by the study's concurrently obtained current ratio, total asset turnover, debt to equity ratio, and firm size.